AN ANALYSIS OF CODE MIXING AND CODE SWITCHING ON LECTURERS’ ACTIVITIES IN THE CLASSROOM - Yayan Yayan (Journal of English Education Program (JEEP), 2017)
This study is intended to investigate the use of code mixing and code switching by the lecturer A and D in their activities in the classroom. In this study, the researcher used Hoffman and Muysken theories. The findings of this study were expected to give some useful insights to English department students in order to get better understanding of the use of code mixing and code switching. The research design of this study is descriptive qualitative and the data of this study is in form of lecturers’ activities. The results showed that there was one type of code mixing and one kind of code switching which were used by the lecturer A. Namely: Insertion code mixing (60%), and Inter-sentential switching (100%). Then, there were two kinds of code mixing and three kinds of code switching which werre used by the lecturer B. Namely: (1) Insertion code mixing (70%), alternation code mixing (30%). And then, (1) inter-sentential switching (30%), (2) intra-sentential switching (30%) and (3) emblematic switching (10%). This study concludes, that insertion code mixing was mosly used by the lecturer A and D. And then, inter-sentential was mostly used by the lecturer A and D, because they prefer to explain their messages used code mixing and code switching from one language to another language between sentences. The results of this study do not involve all aspects of code mixing and code switching on lecturers’ activities. It was expected to the next researcher to include all aspects of it.